2003
DOI: 10.1039/b300607g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of proteins on spherical polyelectrolyte brushes in aqueous solution

Abstract: We consider the adsorption of bovine serum albumin (BSA) on spherical polyelectrolyte brushes (SPB). The SPB consist of asolid polystyrene core of 100 nm diameter onto which linear polyelectrolyte chains [poly(acrylic acid), (PAA)] are grafted. The adsorption of BSA is studied at a pH of 6.1 at different concentrations of added salt and buffer. We observe strong adsorption of BSA onto the SPB despite the effect that the particles as weil as the dissolved BSA are charged negatively. The adsorption of BSA is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
387
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(418 citation statements)
references
References 41 publications
20
387
1
3
Order By: Relevance
“…23 . The Si wafers that served as solid support for planar PAA brushes were purchased from Siliciumbearbeitung Andrea Holm (Tann, Germany).…”
Section: à2mentioning
confidence: 99%
See 2 more Smart Citations
“…23 . The Si wafers that served as solid support for planar PAA brushes were purchased from Siliciumbearbeitung Andrea Holm (Tann, Germany).…”
Section: à2mentioning
confidence: 99%
“…It has been found that the SPB particles bind huge w Presented at the annual meeting of the Deutsche Bunsen-Gesellschaft fu¨r Physikalische Chemie, Dresden, Germany, May 20-22, 2004. amounts of BSA under electrostatic repulsion at low ionic strength. 23 Moreover, BSA that is irreversibly adsorbed at low ionic strength can be desorbed from the SPB particles by rinsing with a 500 mM sodium chloride solution. This observation is rather unexpected, since the elevated ionic strength is shielding the direct electrostatic repulsion between BSA and the SPB particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] In order to test the sensing capability of the TEM grid cell for detecting proteins, small amounts of the lysozyme protein were dissolved in the aqueous phase at pH ¼ 12. Fig.…”
Section: Preparation Of Paa-b-lcpmentioning
confidence: 99%
“…Such high loading capacity can be explained by the diffusion of IgAs through the chitosan shell. This diffusion process can be understood by considering the protein as a multivalent counter-ion interacting with the ammonium groups of the shell, as suggested by Ballauff et al for spherical polyelectrolyte brushes [40] . The concomitant release of monovalent counter-ions induces an entropic gain that counter-balances the repulsive electrostatic interactions and steric hindrance.…”
Section: Discussionmentioning
confidence: 99%